POSSIBILITIES OF ENVIRONMENTAL SUSTAINABILITY IN INTERIOR DESIGN - Briede, Ingūna; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Sustainable design looks at the environmental, social and economic categories in interactions that deliver significant environmental and health solutions. Common trends in society show that sustainable thinking has not yet become a way of life and is fragmented. This justifies the need for both future and existing professionals – architects and environmental / interior designers – to acquire the necessary knowledge and skills in designing and evaluating projects in aspects of sustainability that are related to public health and well-being. The aim of the article is to determine the criteria for the evaluation of sustainable design, which should be taken into account during the development and implementation of the interior design project. Research methods – theoretical – research and analysis of scientific literature.